Exposure to Degludec During Pregnancy : A Case Report (2019)
A non-planned pregnancy in a patient with type 1 diabetes with ocular complications, was treated with degludec from pre-conception stages until the postpartum is reported. The newborn was healthy without any congenital abnormalities; however, due to respiratory distress required neonatal intensive care unit.